Optimal Bundling Strategies Under Heavy-Tailed Valuations - Ibragimov, Rustam; Walden, Johan (Management Science, 2010)
We develop a framework for the optimal bundling problem of a multiproduct monopolist, who provides goods to consumers with private valuations that are random draws from a distribution with heavy tails. We show that in the Vickrey auction setting, the buyers prefer separate provision of the goods to any bundles. We also provide a complete characterization of the optimal bundling strategies for a monopolist producer, who provides goods for profit-maximizing prices. For products with low marginal costs, the seller's optimal strategy is to provide goods separately when consumers' valuations are heavy-tailed and in a single bundle when valuations are thin-tailed. These conclusions are reversed for goods with high marginal costs. For simplicity, we use a specific class of independent and identically distributed random variables, but our results can be generalized to include dependence, skewness, and the case of nonidentical one-dimensional distributions.